Effect of synthesis parameters on structural and thermal properties of NbC/C nano composite synthesized via in-situ carburization reduction route at low temperature. Issue 11 (15th August 2016) - Gupta, Aayush; Singla, Gourav; Pandey, O.P.
Abstract: Core-shell NbC/C nano composite has been synthesized by reacting niobium pentaoxide (Nb2 O5 ) with metallic magnesium and acetone (C3 H6 O). The ensued powder samples are characterized by X-ray diffraction (XRD), differential scanning calorimetry/thermal gravimetric analysis (DSC/TGA), field-emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM) and Brunauer-Emmett-Teller (BET) analysis. The synthesis temperature, holding time and heating rate has been optimized to facilitate the in-situ reduction-carburization of Nb2 O5 . The broadening of XRD diffraction peaks corresponding to NbC is analyzed using Williamson-Hall (W-H) analysis by calculating various parameters such as strain, stress, strain energy density for all the samples. The mean particle size of nano NbC is estimated by Scherrer's criterion which is highly correlated with W-H analysis in less stressed system. The electron microscopy analysis showed that particles have a partial faceted morphology along with carbon layer and having wide particle size distribution. BET analysis depicted large surface area having a combination of micropores and mesopores. All the results of various characterizations have been used to predict the mechanism of formation of core-shell NbC/C nano composite.